Marias que venceram na vida: uma análise da ascensão da mulher negra via escolarização em Salvador/BA - Pereira, Edilene Machado (2008)
In this work It is investigated trajectory of the soteropolitana black woman, women born in the city of salvador/Ba, or that to they had adopted. Objective to give visibility to the trajectories of success of black women in the city of the Salvador-Bahia. When searching the understanding of the trajectories of success of these women and also, of as these processes influences in the construction of its ethnic identities, is looked to show the untiring fight in the search of the full citizenship, in the construction of one another history. Therefore, the work if inserts in the field of the racial relations, perpassando the relations of sort and the processes of identity constitution and subjectivity of the black woman. When treading this way we look for to argue theoretically, concepts as: success, imaginary social representation, identity and race. When searching to understand the trajectory of life of these women (between which I include myself), this work places in the field of the production intellectual-activist who goes alem of the denuncista speech of the situations of discriminations lived for them. The central focus is to give to visibility to the positive processes of fights and conquests, as well as the meaning politician of the being black woman in a marcadamente different society in the access of this social group to the spaces of being able. Over there of this this paper has for objective to not only enumerate the situations of discriminations lived for the women, but, over all, to give to visibility to the positive processes of fights and conquests of the same ones. We look ouviz them with intention to understand the process of construction of its identity, of being successfully professional woman black and social, that reinventaram its lives and today they serve of example for the new generations. This experience was characterized for the verbal visualization of lives deeply of these women, victorious Marias, in a maxista society, racist and sexcista